Hidupkan Kembali Rasa Percaya Diri Korban Bully Melalui Potensi Yang Dimiliki - Elda Febriana; Mia Aulina (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Self-confidence is one aspect of personality that plays an important role in life, especially in the socialization process in society. Adolescence is a golden period for the formation of character or traits and inculcating values ​​in life, however, this period is also prone to unpleasant things and negative effects during the process of absorbing these values. Self-confidence or self-confidence can decrease / decrease if someone experiences something unpleasant, for example experiencing bullying or bullying. The same thing was experienced by one of the children from the Al Washliyah Binjai orphanage, the lack of assistance and openness of SG made his confidence dim because of the bullying case that had happened to him. SG closed the meeting potential because he was not confident, so he hesitated in developing. Armed with the problems above, the practitioner makes a decision by providing services/assistance using the casework intervention method which includes various stages including engagement, intake, and contract (EIC) as the initial stage and ends with the termination stage.